Optimization of cogeneration capacity by adding crop residues to bagasse in typical Peruvian sugar industry - Gonzales Chávez, Salome (2019)
In this work, an energetic evaluation of appropriate mixture of cane harvest waste / sugarcane bagasse was carried out to improve the cogeneration capacity of both electricity and steam for the sugar production process in a typical Peruvian sugar industry. Peru has a tradition in the sugar industry characterized by its high sugarcane plantation productivity; However, the problem that persists to the present is the poor form of cane harvest (pre-burned cane in the field) and obsolescence technology used in cogeneration process.  The methodology begins with the mechanized harvesting in pilot area of cane plantation, followed by preparation and drying processes of harvest residues. Samples of waste are taken to laboratory for physicochemical and energetic characterization at different moisture conditions, obtaining calorific value and elemental content values. The appropriate waste / bagasse mixture that feeds the boiler was selected to proceed with the energy tests of Cogeneration Plant. As result, for an optimized fuel mixture, crop residues / bagasse in a volumetric ratio 1/4, the increase in steam production is achieved comparatively to combustion of bagasse alone. In electricity generated represents an increase from 13 to 18 MW, an increase in cogeneration efficiency of 22.5% and a reduction in cogeneration cost of 19%.  In this work, an energetic evaluation of appropriate mixture of cane harvest waste / sugarcane bagasse was carried out to improve the cogeneration capacity of both electricity and steam for the sugar production process in a typical Peruvian sugar industry. Peru has a tradition in the sugar industry characterized by its high sugarcane plantation productivity; However, the problem that persists to the present is the poor form of cane harvest (pre-burned cane in the field) and obsolescence technology used in cogeneration process.   The methodology begins with the mechanized harvesting in pilot area of cane plantation, followed by preparation and drying processes of harvest residues. Samples of waste are taken to laboratory for physicochemical and energetic characterization at different moisture conditions, obtaining calorific value and elemental content values. The appropriate waste / bagasse mixture that feeds the boiler was selected to proceed with the energy tests of Cogeneration Plant.  As result, for an optimized fuel mixture, crop residues / bagasse in a volumetric ratio 1/4, the increase in steam production is achieved comparatively to combustion of bagasse alone. In electricity generated represents an increase from 13 to 18 MW, an increase in cogeneration efficiency of 22.5% and a reduction in cogeneration cost of 19%.